US-China Trade War: Indonesia as a Muslim Majority Country and Vietnam Responses - Ivan, Muhammad; Paksi, Arie Kusuma (POLITEA, 2020)
This research discusses the responses of countries in Southeast Asia in the context of US-China trade war, with particular focus on what strategies taken by Indonesia (as a Muslim majority country) and Vietnam government to apply and attract investment from US and China as a result of trade war among them. The writer chose qualitative method to get an in-depth data and find the dynamic problems and a strategy taken by a country to overcome the problem caused by trade war. By Using mercantilist approach this paper argues that both Indonesia and Vietnam have a different strategies in order to gain the foreign investor to come to their countries and manage to maintain the sustainability in the middle of trade war escalation. As a result both Indonesia and Vietnam have succeeded in maintaining their economic stability through the strategies they have adopted which have resulted positive.